Speech and language assessment in adult cochlear implant candidates and users - Lucie Nohová; Julie Čefelínová (Listy klinicke logopedie, 2020)
In the Czech literature there is a lack of information about speech and language assessment in adult cochlear implant (CI) candidates and users. The article presents the issue of adult cochlear implantation from a speech and language therapist perspective. The paper points out the current changes in the CI candidacy, which have opened the possibility to provide cochlear implantation to other types of patients, including bilateral implantation in adults. The aim of the article is to present an overview of diagnostic tools used abroad. Moreover, it provides the information about the current pre- and post-implantation possibilities in terms of speech and language evaluation in Czechia.